The Effects of Lean Management in Life Cycle Management Practices towards Sustainability Performance in Indonesia Pulp and Paper Industry - Haizam Mohd Saudi, Mohd; Hutomo Mustika Djaya, Arry; Syifa Puspani, Nissa; Sinaga, Obsatar; ., . (International Journal of Engineering and Technology, 2018)
Lean management practices become incredibly important for organizations to associate with lifecycle management practices. This is due to the facts that financial statement alone would not be sufficient, but it is also vital for companies to analyze the economic, social and environmental aspects of the company's operations. Researchers produced a conceptual framework by using Stakeholder and Legitimacy theory. The Life Cycle Management (LCM) is being measured by using lean management to improve the production of the firms. The research tested 62 companies from pulp and paper industry from Indonesia.Â This research also consists of 248 samples utilizing primary and secondary data. Finding reveals, a phenomenon with role of sustainability report disclosure and lean management practices adoption have significant effects on products lifecycle management practices towards enhancing sustainability performance. Moreover, our results yield insights to optimize the employeesâ€™ sustainability performance in the pulp and paper industry. The result of the research indicates that lean management has been identified, as the mediator for the enhancement of sustainable performance in the pulp and paper industry in Indonesia.Â Â Â